2020
DOI: 10.3386/w27975
|View full text |Cite
|
Sign up to set email alerts
|

Milton Friedman and Exchange Rates in Developing Countries

Abstract: have been extremely useful. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As part of an official mission sent by the Eisenhower Administration, in 1955 Friedman traveled to India to advise the government on economic issues (Edwards, 2020). His advice was summarized in a 11-page memo he submitted to the Nehru government in November of that year.…”
Section: Friedman Reiterated This Position In Favor Of Flexible Excha...mentioning
confidence: 99%
See 2 more Smart Citations
“…As part of an official mission sent by the Eisenhower Administration, in 1955 Friedman traveled to India to advise the government on economic issues (Edwards, 2020). His advice was summarized in a 11-page memo he submitted to the Nehru government in November of that year.…”
Section: Friedman Reiterated This Position In Favor Of Flexible Excha...mentioning
confidence: 99%
“…As Edwards (2020) has pointed out, at this time Friedman had a limited understanding of the currency and monetary issues facing developing countries. His perspective was entirely US centric and rather simplistic.…”
Section: Friedman Reiterated This Position In Favor Of Flexible Excha...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been suggested that the current international debt crises were strongly influenced by the improper exchange rate policies implemented around the turn of the millennium (Edwards et al, 2003). According to Edwards (2020), a fixed exchange rate system was a major contributing factor to Chile's currency and financial crises. Undeniably, stability in the RER is a key aspect in improving a country's trade sector, and in enhancing the overall macroeconomic stability and performance of a country (Conrad and Jagessar, 2018;Mahraddika, 2020 andFidora et al, 2021).…”
Section: Introductionmentioning
confidence: 99%